Addressing Regional Disparities in High School Entrepreneurship Education in a Developing Country - Ahmi Husein, Muhammad; Araminta, Lavinia Disa Winona; Nur Arumsari, Devinta (Journal of Economics, Business, and Government Challenges, 2025)
Entrepreneurship education is a critical driver of entrepreneurial skills and mindsets, yet its implementation often faces inequities, particularly in developing countries like Indonesia. Urban high schools, primarily on Java Island, benefit from practical learning opportunities, while rural and underdeveloped regions lack resources and access. This study investigates these disparities by exploring the experiences of university students enrolled in business-related courses about the entrepreneurship education gained during high school across diverse provinces. Using purposive sampling and inductive thematic analysis, the research captures perspectives from both developed and underdeveloped regions, highlighting the inequitable access to entrepreneurial opportunities. The findings show that urban schools provide more hands-on activities, like product creation and market engagement, while rural students face fewer opportunities and resources. The study highlights the need for practical learning methods and blended approaches to reduce these gaps. By offering insights for policymakers, this research aims to promote fair and effective entrepreneurship education programs. Addressing these regional disparities could make entrepreneurship education a powerful tool for socio-economic development, empowering students across Indonesia and fostering innovation in underserved areas.